Implementation of Carbon Accouting and Green Innovation in Improving Environmental Performance Against the SDGs in Companies - Maharani, Dorifahtu Afirstantian; Rahayuningsih, Sri (CV. Lenggogeni Data Publishing, 2025)
Seeing the importance of carbon accounting and green innovation in the context of environmental performance and compliance with SDGs, this analysis is very relevant to provide new insights into how these two aspects can support each other. It is hoped that this analysis can provide practical recommendations for companies in implementing carbon accounting and green innovation effectively, as well as help them achieve the sustainability goals that have been set. The aim of this analysis is to find out and analyze how carbon emissions and green innovation impact the Sustainable Development Goals. In addition, this analysis also investigates how environmental performance impacts the relationship between the creation of carbon emissions and green innovation towards the SDGs. This analysis discusses energy and infrastructure companies listed on the Indonesia Stock Exchange from 2020 to 2022. A purposive sampling technique was employed for this investigation, and a sample of 14 businesses was selected. for this study, a sample of 14 businesses was selected. A total of 14 companies were selected as samples for this research using purposive sampling techniques. The PLS hypothesis testing system is used, and secondary data is the type of data used. The results of the analysis show that sustainable development goals are influenced by environmental performance and carbon accounting. On the other hand, green innovation has a significant impact regarding the environmental performance of companies working in the energy and infrastructure sectors.